A comparison of computer‐assisted and therapist‐led instruction for children with autism spectrum disorder. (20th February 2017) - LeBlanc, Brittany A.; Kodak, Tiffany; Cariveau, Tom; Campbell, Vincent
Abstract : The current investigation applied a model of assessment‐based instruction to an evaluation of the efficacy and efficiency of computer‐assisted and therapist‐led instruction on skill acquisition for 3 participants with autism spectrum disorder. We also evaluated the participant's attending during instruction and the social validity of each format of instruction. The results showed that computer‐assisted instruction was most efficient for 2 of the 3 participants, although attending varied across instructional formats. In addition, the social validity of instructional formats varied across participants.